EVALUASI PENERAPAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DI RSUD K.H MANSYUR KINTAP KALIMANTAN SELATAN - Ranchika May Irtanida; Ardhitya Yoga Pramantara (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to evaluate the implementation of the Hospital Management Information System (SIMRS) at RSUD K.H. Mansyur Kintap, South Kalimantan, as an effort to improve service effectiveness and administrative efficiency within the hospital. The research employs a descriptive qualitative approach through interviews, observations, and document studies involving system users, including medical staff, administrative officers, and IT personnel. The results indicate that the implementation of SIMRS has contributed to faster patient registration processes, better management of medical record data, and improved hospital financial reporting. However, several challenges were identified, such as insufficient user training, limited network infrastructure, and suboptimal integration between system modules. Overall, the implementation of SIMRS at RSUD K.H. Mansyur Kintap is considered fairly effective, but improvements in human resources and technical support are still needed to ensure optimal and sustainable system performance.